Pengisian Jabatan Penjabat Kepala Daerah Oleh Pejabat Tinggi Tentara Nasional Indonesia - Alwi Reniwuryaan; Marthinus Johanes Saptenno; Vica Jillyan Edsti Saija (Faculty of Law Universitas Pattimura, 2023)
On May 24, 2022 the Governor of Maluku appointed Brigjen TNI andi Chandra As’adudin as Acting Regent of West Seram through Minister of Home Affairs Decree Number: 131.81-1164 of 2022 concerning the appointment of the acting regent of West Seram. To review and analyze the filling of the position of acting regional head by high ranking officials of the Indonesian National Armed Forces whether or not it complies with the laws and regulations in Indonesia and the legal consequences of filling the positions of acting regional heads by high ranking officials of the Indonesian National Armed Forces. The research method used is normative juridical, using a statutory approach and a conceptual approach. The legal materials used in this paper are primary, secondary and tertiary legal materials. The research method used is normative juridical, using a statutory approach and a conceptual approach. The legal materials used in this paper are primary, secondary and tertiary legal materials. Filling in the position of Acting regional head by a high ranking official of the Indonesian National Armed Forces is not in accordance with or contrary to a number of laws and regulations which mandate that the filling of a high ranking position must be accompained by a Presidential Decree on Appointment of Acting Governor and Minister of Home Affairs Decree on Appoinment of Acting Regent/Mayor is invalid and legally flawed.